1997
DOI: 10.1016/s1063-4584(97)80002-7
|View full text |Cite
|
Sign up to set email alerts
|

The Bristol ‘OA500’ Study: progression of osteoarthritis (OA) over 3 years and the relationship between clinical and radiographic changes at the knee joint

Abstract: Five hundred patients with established, symptomatic limb joint OA have been recruited into an on-going prospective study of the natural history of the condition. Four hundred and fifteen patients (mean age 65.6 years, female to male ratio 2.05:1) were available for a full clinical and radiographic review 3 years after entry (mean entry to follow-up interval 37.6 months, range 31-41). The majority reported an overall worsening of their condition, although pain severity did not change. There was an overall incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
171
4
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 244 publications
(184 citation statements)
references
References 22 publications
6
171
4
3
Order By: Relevance
“…In contrast to the review on prognostic factors of progression of hip OA by Lievense et al (5), we found only 4 studies (15%) that also used a clinical outcome for progression of knee OA (11,19,23,24,45). The study by Dieppe et al (11) did not include persons with a total knee replacement in the analysis; the other 4 studies used either a radiologic change or a total knee replacement in their definition for progression of knee OA (19,23,24,45).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In contrast to the review on prognostic factors of progression of hip OA by Lievense et al (5), we found only 4 studies (15%) that also used a clinical outcome for progression of knee OA (11,19,23,24,45). The study by Dieppe et al (11) did not include persons with a total knee replacement in the analysis; the other 4 studies used either a radiologic change or a total knee replacement in their definition for progression of knee OA (19,23,24,45).…”
Section: Discussioncontrasting
confidence: 87%
“…Progression was defined as radiologic progression in almost all studies. Only 4 studies (11,19,23,24,45) (15%) also reported on a clinical outcome (total knee replacement).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Glucosamine/Chondroitin Arthritis Intervention Trial, over 2 years only 19 -22% of participants had JSN Ͼ0.48 mm (15). Over 3 years, in an older group of 68 individuals in Japan, JSN was evident in 32% of knees (16); this was similar to the proportion (31%) of those exhibiting JSN Ͼ2 mm over 3 years in the Bristol OA500 study (17). Sahlstrom et al reevaluated 110 (of 256 individuals) who had radiographs for knee pain between 1970 and 1973 at a university hospital and who remained untreated or conservatively treated.…”
Section: (3)mentioning
confidence: 56%